Leber hereditary optic neuropathy - Liutkevičienė , R.; Sidaraitė, A.; Kozlovskaja , I.; Ašmonienė , V.; Jurkutė , N. (Neurologijos seminarai, 2018)
Leber hereditary optic neuropathy (LHON) is one of the most common inherited mitochondrial optic neuropathies, caused by mitochondrial DNA mutations. Three most common mutations, namely m.11778G>A, m.14484T>G, and m.3460G>A, account for the majority of LHON cases. These mutations lead to mitochondrial respiratory chain complex I damage. Typically, LHON presents at the age of 15–35 years, with male predominance. LHON is associated with severe, subacute, and painless bilateral vision loss and accounts for one of the most common causes of legal blindness in young individuals. Spontaneous visual acuity recovery has been reported in patients harbouring m.14484T>C mutation, however, this inherited optic neuropathy results in irreversible vision loss. Up to date LHON treatment is limited. Idebenone has been approved by EMA to treat LHON. However, better understanding of disease mechanisms and ongoing treatment trials are promising and brings hope for patients. In this article we summarize clinical presentation, diagnostic features, and treatment of LHON.